2021
DOI: 10.1111/jog.14700
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recombinant klotho in cisplatin‐induced ovarian failure in mice

Abstract: Aim To investigate whether recombinant klotho given concomitantly with cisplatin is effective in preventing cisplatin‐induced ovarian damage. Methods Thirty‐two adult female mice were divided into four groups. Saline was given to the first group, cisplatin to the second group, recombinant mouse klotho to the third group, and recombinant mouse klotho + cisplatin to the fourth group. The removed ovarian tissues were examined and groups were compared histologically and immunohistochemical examination for antimull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The pathogenesis of DOR is complex, and no unified animal model could be used on the study of DOR. Chemotherapy for oncological reasons is one of the common causes of DOR [19]; thus, cisplatin (CDDP, a chemotherapeutic drug) has been reported to be one of the most common methods to induce DOR with a shorter modeling cycle and typical pathological changes [33,34]. In the study, 1.0 mg/kg/day CDDP treatment for 5 consecutive days could cause an estrous cycle disorder, a decrease in the number of antral follicles and corpora lutea, an increase in the serum FSH level, and a decrease in the serum E 2 and AMH levels in mice, which were largely consistent with the clinical features of DOR patients, indicating that the in vivo model was successfully established and suitable to be used on the study of DOR.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of DOR is complex, and no unified animal model could be used on the study of DOR. Chemotherapy for oncological reasons is one of the common causes of DOR [19]; thus, cisplatin (CDDP, a chemotherapeutic drug) has been reported to be one of the most common methods to induce DOR with a shorter modeling cycle and typical pathological changes [33,34]. In the study, 1.0 mg/kg/day CDDP treatment for 5 consecutive days could cause an estrous cycle disorder, a decrease in the number of antral follicles and corpora lutea, an increase in the serum FSH level, and a decrease in the serum E 2 and AMH levels in mice, which were largely consistent with the clinical features of DOR patients, indicating that the in vivo model was successfully established and suitable to be used on the study of DOR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies in this field in recent years have pointed out that the induction and development of endoplasmic reticulum pressure in ovarian GC go hand in hand in the ubiquitination course of specific molecules in cells [12] . GC cells play a vital role in biological course, but the role of TP5 in GC has not been thoroughly studied [13,14] . In this study, we found that TP5 was helpful to maintain the steady state of GCs endoplasmic reticulum and provide a stationary internal environment for follicular advancement.…”
Section: Groupmentioning
confidence: 99%